2021
DOI: 10.32628/cseit217475
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Prediction Using Twitter Sentiment Analysis

Abstract: Stock market prediction is an important topic in ?nancial engineering especially since new techniques and approaches on this matter are gaining value constantly. In this project, we investigate the impact of sentiment expressed through Twitter tweets on stock price prediction. Twitter is the social media platform which provides a free platform for each individual to express their thoughts publicly. Specifically, we fetch the live twitter tweets of the particular company using the API. All the stop words, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Researchers have used social media data for a wide range of purposes-from predicting postpartum depression from Facebook posts (De Choudhury et al, 2014) to trying to predict movements in the stock market based on the sentiment of Tweets (Mittal & Goel, 2010). However, not all uses of social media data have been welcomed by users or seen as acceptable in the research community.…”
Section: Public Data Usementioning
confidence: 99%
“…Researchers have used social media data for a wide range of purposes-from predicting postpartum depression from Facebook posts (De Choudhury et al, 2014) to trying to predict movements in the stock market based on the sentiment of Tweets (Mittal & Goel, 2010). However, not all uses of social media data have been welcomed by users or seen as acceptable in the research community.…”
Section: Public Data Usementioning
confidence: 99%
“…These studies targeted US stock market and took all kinds of tweets together. Sannakki and Sambrekar (2021) also were able to find a statistically significant relationship between changes in daily stock price and tweets polarity. They made sentiment analysis on tweets to polarize them into two groups.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Also, they observed that the effect of negative sentiment lasts more than the positive one. Padmanayana et al (2021) achieved 89.8% accuracy in predicting stock prices with sentimental analysis. They collected tweets about sixteen companies and fed these tweets into a machine learning model to classify them into three labels and generate prediction value which was then correlated with stock values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Twitter data reveals how companies are responding to macromarketing changes like sustainability. Twitter data has been used to analyze a myriad of topics, such as financial issues (Daniel et al, 2017), stock performance (Mittal and Goel, 2012), political campaigns (Budiharto and Meiliana, 2018), sentiments towards disease (Gabarron et al, 2019), branding (Ghiassi et al, 2013), COVID-19 (Rahman et al, 2021) and more.…”
Section: Methodsmentioning
confidence: 99%